The effects of Otago exercise on prevention of falls in patients with artificial arthroplasty: A Meta-analysis (奥塔戈运动对人工关节置换术患者跌倒预防效果的Meta分析) - (王蒙); WANG Yafei (王亚飞); ZHAO Yemeng (赵叶梦) (中西医结合护理)
Objective To provide evidence-based basis for rehabilitation program of patients with artificial arthroplasty by Meta-analysis of the effect of Otago exercise on prevention of falls. Methods By searching Pubmed, The Cochran Library, Web of Science, EMBASE, CNKI, CJFD, Wanfang Data and VIP, randomized controlled trials published in Chinese and English until May 2021 were included. Two researchers screened, extracted and evaluated the literature, and the included literature was analyzed by Meta-analysis using RevMan 5. 3 software. Results A total of 467 patients were included in 6 Chinese literatures. The falls prevention efficacy of Otago exercise in patients after artificial arthroplasty［SMD = 0. 65, 95% CI (0. 37, 0. 93), P < 0. 01］, balance ［MD = 3. 23, 95% CI (2. 18, 4. 28), P< 0. 01］, knee joint function ［MD = 10. 32, 95% CI (9. 52, 11. 13), P< 0. 01］, self-care ability ［MD = 4. 98, 95%CI (3. 53, 6. 43), P<0. 01］ all showed significant improvement, with statistically significant differences. Conclusion Otago exercise can not only improve the falls prevention efficiency and balance force of patients after artificial arthroplasty, but also improve the joint function and life self-care ability. However, the quantity and quality of the literature included in this study were limited. Randomized controlled trials with larger sample size are still needed to verify the rehabilitation effect of Otago exercise on artificial joint replacement. (目的 通过对奥塔戈运动对人工关节置换术患者跌倒预防效果进行Meta分析, 为人工关节置换术患者实施康复计划提供循证依据。方法 通过检索中英文数据库Pubmed、The Cochran Library、Web of Science、EMbase, 中国知网(CNKI)、中国期刊全文数据库(CJFD)、万方数据 (Wandang Data)和维普数据(VIP), 收集截止到2021年5月的中英文随机对照试验。由两名研究人员对文献进行筛选、数据提取和评价, 对纳入的文献通过RevMan5. 3软件进行Meta分析。结果 共纳入6篇中文文献, 共有患者467例。奥塔戈运动对人工关节置换术后患者的跌倒效能［SMD=0. 65, 95%CI(0. 37, 0. 93), P＜0. 01］、平衡力［MD=3. 23, 95%CI(2. 18, 4. 28), P＜0. 01］、膝关节功能［MD=10. 32, 95%CI(9. 52, 11. 13), P＜0. 01］和生活自理能力［MD=4. 98, 95%CI(3. 53, 6. 43), P＜0. 01］均有显著改善。结论 奥塔戈运动不仅能有效提高人工关节置换术后患者的跌倒效能和平衡力, 对关节功能和生活自理能力均有改善作用。但本研究纳入文献的数量和质量有限, 仍需要更大样本的随机对照试验来对奥塔戈运动对人工关节置换术的康复作用进行验证, 从而提供更为可靠的循证依据。)